2012
DOI: 10.1109/twc.2011.110711.102126
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth Sharing for Relaying in Cellular Systems

Abstract: Abstract-We investigate bandwidth allocation in next generation cellular systems employing relays similar to LTE advanced systems with type-I relays. We jointly optimize the bandwidth and power usage under constraints on required rate, bandwidth and transmit power. We study scenarios wherein, the relay acts as a forwarder for multiple User Equipments (UEs/users) in both uplink and/or downlink. This includes scenarios when the relay has its own data to send along with forwarding the data of other users. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
(28 reference statements)
0
20
0
6
Order By: Relevance
“…Recently, a category of algorithms for the joint capacity (or bandwidth) and power allocation has been introduced. A large number of publications concerning this topic can be found in the literature [5], [13], [14], [15], [16], [17], [6] and [18]. For the sake of simplicity, we have conveyed the various algorithms, of this category, into two groups with similar formulations of the allocation problem.…”
Section: The Resource Allocation Methods Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a category of algorithms for the joint capacity (or bandwidth) and power allocation has been introduced. A large number of publications concerning this topic can be found in the literature [5], [13], [14], [15], [16], [17], [6] and [18]. For the sake of simplicity, we have conveyed the various algorithms, of this category, into two groups with similar formulations of the allocation problem.…”
Section: The Resource Allocation Methods Groupsmentioning
confidence: 99%
“…It is aimed at minimizing the transmitted power by allocating bandwidth, in [Hz], among entities. We call it Power Minimization (PM) and the approach can be found in [17], [6], [13] and [18]. From the analytical viewpoint, the allocation problem is modeled as follow (2):…”
Section: B Power Minimization (Pm) With Constrained Capacity Groupmentioning
confidence: 99%
“…However, it is shown that it is not the best possible performance and better performance and more improvements can be achieved by optimising the relevant power control parameters. Optimising output power and bandwidth allocation in relaying networks, considering type 1 relays are investigated in [225,226]. It is shown that deploying the bandwidth sharing method in LTE-Advanced networks can provide about 3.5 dB gain in the transmit power in comparison with the case in which fixed bandwidth is allocated.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…The system performance enhancement of LTE-A and intercell interference mitigation is shown to be achieved by applying the power control scheme both at the DeNodeBs and the RNs. Out-band relaying operations performance optimization is investigated in [18]. In [19], the reduction in relaying latency is discussed by extending the available relaying schemes.…”
Section: Relaying In Long Term Evolution Advanced (Lte-a)mentioning
confidence: 99%